How to Create Effective and Efficient Naá¸¥wu Media with Short Videos Based on the Camtasia Application? - Handayani, Eka Utari; Utami, Rika Lutfhiana; Tamsil, Irvan Maulana (Departemen Pendidikan Bahasa Arab, 2021)
Language learning is a complex process and requires extra effort. The limited allocation of learning duration is the root of the problem; At the beginner level, the naá¸¥wu rules are considered very difficult, especially for students from public schools and have never studied Arabic previously. Making videos based on the Camtasia Studio 8 application is one of the ways to encourage students to comprehend, leading to mastery of the naá¸¥wu rules. This study used the waterfall method, which consisted of requirements and analysis, design, implementation and unit testing, system testing, operation, and maintenance. This research aims to create learning media that is relevant to the era, effective, and efficient. The result indicates that video media is quite efficient and effective in supporting students' understanding of naá¸¥wu rules. This three-minute video can contain materials and examples within a short duration. Hence, the students do not get bored quickly and can focus on listening to it.